A Study of Alex Rose’s Self Actualisation in The Life List (2025) Using Kaufman’s Theory - Astrialesta Aisyah Nugraha; Dwi Nur Cahyani Sri Kusumaningtyas (Universitas Negeri Surabaya, 2026)
This article examines Alex Rose's self-actualisation journey in Adam Brooks's film The Life List (2025) through Scott Barry Kaufman's contemporary theory of human needs. The study focuses on how Alex's internal conflicts create tensions between security needs and growth needs, and how her development later moves toward transcendence. Using a qualitative film analysis and close reading method, the data were taken from selected dialogues, scenes, subtitles, and narrative events that reveal Alex's psychological development. The analysis shows that Alex's dependence on her mother, fear of leaving her comfort zone, identity crisis after learning the truth about her biological father, disappointment with Johnny, and conflict with Garrett function as turning points in her movement toward self-understanding. These conflicts reveal unstable security needs, especially safety, connection, and self-esteem, while gradually opening the possibility of growth through exploration, love, and purpose. The article further finds that Alex's journey does not end in personal fulfilment. Her growth develops toward transcendence when she shares her mother's messages with her brothers, reconciles with Samuel, accepts grief, and forms a broader community of love and meaning. The film therefore represents self-actualisation as a dynamic, relational, and non-linear process rather than a final achievement.